What I was told : investigating how verbatim- and physical theatre can be combined to portray ethnographic research of gender performativity under female students at Stellenbosch University - Baard, Helena (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.